Features of Conceptualization and Categorization of Verbal Synonyms for ‘Providing Medical Assistance’ in Contemporary Russian - A. A. Galiuk; E. I. Zinovieva (Научный диалог)
This article is dedicated to the exploration of the conceptualization of the process of providing medical assistance through an analysis of the synonyms лечить [lechit’] (‘to treat’), врачевать [vrachevat’] (‘to heal’), and исцелять [istselyat’] (‘to cure’) in order to identify the peculiarities of their categorization within a synchronic perspective of the Russian. The novelty of this study lies in the application of a cognitive-discursive approach to uncover the conceptual characteristics of these lexemes, allowing for a characterization of the verbs based on their cognitive and communicative functions. The relevance of this research is underscored by the inclusion of the examined verbs in an important lexical-semantic group of assistance verbs, as well as the insufficient informative nature of the descriptions provided in Russian explanatory dictionaries and synonym dictionaries. The authors delineate the boundaries of the synonymic group, analyzing situational, cognitive-semantic, stylistic, grammatical, and discursive features of the verbs, while modeling their cognitive scenarios. The categorization features of these verbs are as follows: lechit’ verbalizes the idea of physical healing, which may be subject to evaluation by an observer; vrachevat’ implies healing by an individual possessing a special gift through traditional methods; istselyat’ suggests the removal of physical and mental ailments by another subject with divine assistance or through inanimate objects, utilizing verbal and tactile means of influence in the former case.